2021
DOI: 10.3390/jcm10225453
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Gender and COPD on the Incidence and Mortality of Hospital-Acquired Pneumonia. A Retrospective Cohort Study Using the Spanish National Discharge Database (2016–2019)

Abstract: Background: We aim to analyze incidence and outcomes of patients hospitalized with hospital-acquired pneumonia (HAP) according to chronic obstructive pulmonary disease (COPD) status and sex in Spain (2016–2019). Methods: We conducted a retrospective cohort study using national hospital discharge data of patients ≥40 years with a primary diagnosis of HAP, using the specific diagnostics of non-ventilator (NV)-HAP and ventilator-associated pneumonia (VAP). Results: We identified 37,029 patients with HAP ((NV)-HAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Non-ambulatory status and COPD have also been shown to be risk factors in previous studies [ 33 ]. In our study, COPD grade showed a clear dose-response association with MDR pneumonia development; therefore, the association may be robust [ 34 , 35 ]. Being underweight and having bedsores are indications of malnutrition in patients, making them prone to infection with MDR pathogens.…”
Section: Discussionmentioning
confidence: 97%
“…Non-ambulatory status and COPD have also been shown to be risk factors in previous studies [ 33 ]. In our study, COPD grade showed a clear dose-response association with MDR pneumonia development; therefore, the association may be robust [ 34 , 35 ]. Being underweight and having bedsores are indications of malnutrition in patients, making them prone to infection with MDR pathogens.…”
Section: Discussionmentioning
confidence: 97%
“…Sex differences in the incidence of HAP exist ( 31 ), with men being a risk factor for HAP ( 32 , 33 ), but a lower incidence of non-ventilator HAP in women ( 34 ). Some pathologies may be explained by these differences induced by genders, such as immune response to the virus ( 24 ), diabetes ( 35 ), or chronic obstructive pulmonary disease (COPD) ( 36 ). However, there are few studies on gender differences in risk factors related to hospital-acquired pneumonia (HAP) in SCZ patients with mECT around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Although COPD compromises the lungs, it also has significant systemic consequences [ 1 , 4 , 5 , 6 ]. COPD patients often adopt a sedentary lifestyle that can precipitate the onset of muscle deconditioning through inactivity and a cycle of clinical deterioration [ 1 , 7 , 8 , 9 ], negatively impacting the quality of life of patients with COPD [ 1 , 10 ].…”
Section: Introductionmentioning
confidence: 99%